An uneasy assemblage: Prisoners, animals, asylum-seeking children and posthuman packaging. (March 2015) - Bone, Jane; Blaise, Mindy
Events in Australia have acted as provocations to thinking about the consequences of becoming a 'package' and then being processed. The image of the human, as prisoner, together with narratives about the child and the nonhuman animal as package, are used here in order to understand the world we share with others. These disparate elements are gathered together to form an uneasy assemblage. Thinking through Gilles Deleuze and Felix Guattari, a posthuman performative methodology is used to create this assemblage with its flows, images and stories. Posthumanism presents a challenge that recognizes the possibility of being in the world in a connected/entangled/knotted way. The work of Donna Haraway, Cary Wolfe and Karen Barad underpins the theoretical and methodological perspective. Drawing on evidence from the media, the internet, human and animal rights work and visual representations, this work considers what it means to be packaged, commodified and de-humanized/de-animalized. Once packaged certain experiences become normalized and the (re)packaging of people and animals proliferates and emerges in new iterations. This article argues that by following the flows that circulate around the packaged animal or human everything changes, and becoming part of the assemblage invites active engagement with the unease that emerges. In this process our response-ability is called into question along with aspects of a relational ethics.